The Effect of Shopee E-Commerce Service Quality on Consumer Satisfaction in Shopee Indonesia Users in Surabaya - Margareta Anggreina; Syamsul Arifin; Komarun Zaman (Journal Social Society, 2026)
The rapid growth of e-commerce in Indonesia has changed consumer shopping behavior from traditional stores to digital platforms. Among the various e-commerce platforms that exist, Shopee has experienced significant growth and has become one of the most widely used platforms by consumers. The quality of electronic services is one of the important factors to maintain customer satisfaction and competitiveness in the e-commerce market. The creation of customer satisfaction can have a positive impact, including the relationship between the company and customers to be harmonious, thus causing customer loyalty. This research aims to examine the influence of Shopee’s e-commerce service quality on customer satisfaction among users in Surabaya. The research employs a quantitative approach. The target population includes Surabaya residents who have utilized the Shopee mobile application. Through Google Forms distributed by the researcher, data was collected from 100 Surabaya residents who had made online purchases via Shopee. The Lemeshow formula was applied to determine the sampling method. Data gathering involved reviewing existing literature, document analysis, and distributing questionnaires. The survey instruments were then assessed for validity, reliability, and normality. Analysis was conducted using normality testing and simple regression through the Statistical Product and Service Solution (SPSS) software. The results of the research supported the proposed hypothesis, revealing a positive and significant relationship. Consequently, it can be concluded that the quality of Shopee's online services significantly and positively impacts customer satisfaction among Shopee users in Surabaya.